Mentoring Language Student-Teachers: A Narrative Perspective to Mentors' Experiences From Borders and Cracks - Edgar Aguirre-Garzón; Diego Ubaque-Casallas (Universidad Nacional de Colombia, 2022)
This narrative study analyzes two mentors' experiences in their mentoring practices with language student-teachers in a private university in Bogotá (Colombia). Employing life-story interviews and drawing on ways of thinking and theorizing from praxis as a standpoint to enact decoloniality, we approach mentors' narratives from the notion of crack. Findings reveal that, for mentors, mentoring practices represent a space for knowledge reconfiguration, a locus of collective knowledge construction, and territories where student-teachers can mobilize and exercise their agency. Overall, when making meaning of clashing experiences in mentoring, mentors have constructed ways to fracture traditional and hegemonic logics of seeing knowledge and the self in teacher education.